Metal cored welding wire for laser cladding and preparation method and application thereof
By using laser cladding technology on the surface of the hydraulic support to form a cladding layer with high Cr content and Mo and Nb combined solid solution strengthening, the problem of hydraulic support being susceptible to chloride ions, H2S corrosion and coal particles in a high Cl-corrosive environment is solved, and the effect of high hardness and excellent corrosion resistance is achieved.
Patent Information
- Application Number
- CN202211689889.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The hydraulic support in coal machine equipment is susceptible to chloride ions, H2S corrosion and coal particles wear in a high Cl-corrosive environment, resulting in premature failure.
Using metal flux-core welding wire for laser cladding, a cladding layer with high Cr content and Mo and Nb combined solid solution strengthening is formed on the surface of the hydraulic support through laser cladding technology, which improves its ability to resist chloride ion corrosion and coal particle wear.
It achieves high hardness and excellent corrosion resistance on the surface of the hydraulic bracket, with a hardness of HRC50 and a neutral salt spray corrosion resistance of more than 1000 hours, significantly extending the service life of the equipment.
Smart Images

Figure CN115922148B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and specifically relates to a metal flux-cored welding wire for laser cladding, and a preparation method and application thereof. Background Art
[0002] Coal is one of the most important energy sources for economic development, but due to its chemical properties, it has a certain degree of corrosiveness. At present, high-corrosion mines are mainly common in Huaibei, Binzhou, Shaanxi and other areas. Compared with Shaanxi, northern Shaanxi, Inner Mongolia and other areas with less gas Cl - The geological environment of coal mines with low ion content is more complex. - Content exceeds 1000mol / L, HCO3 - Content exceeds 500mol / L, SO4 2- The content exceeds 3000mol / L, and the mechanical corrosion resistance is required to be higher. In such coal mines, the safety and stability of the mechanical equipment used for coal mining determines the efficiency and cost of coal mining.
[0003] Among coal mining equipment, hydraulic support is one of the main equipment in coal mining production. However, high Cl - The complex environment of corrosive coal mines makes the surface of hydraulic support equipment more prone to rust, which seriously affects the production of local coal mines. In-depth analysis of its failure mode found that it was mainly caused by the corrosion of chloride ions and H2S and the wear of coal particles. The combination of the two led to the premature failure of hydraulic supports in high-corrosion mines. Therefore, improving its resistance to failure due to the above two factors is a prerequisite for ensuring the safety of hydraulic supports in high-corrosion mines. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a metal flux-cored welding wire suitable for laser cladding and a preparation method and application thereof, so as to solve the problem in the prior art that the bracket in the coal mining equipment is easily corroded by chloride ions, H2S corrosion and coal particle wear.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A metal flux-cored welding wire for laser cladding, comprising a flux core and a welding skin, wherein the flux core is wrapped by the welding skin; the flux core is in powder form, and the welding skin is made of stainless steel;
[0007] The metal flux-cored welding wire is used for preparing a cladding layer by laser cladding; the composition of the cladding layer is, by mass fraction, C: 0.17-0.26%; Si: 0.31-0.43%; Mn: 0.95-1.21%; Cr: 20.18-21.67%; Ni: 1.53-2.08%; Mo: 1.64-2.31%; Nb: 1.03-1.68%; and Cu: 0.90-1.32%.
[0008] A further improvement of the present invention is:
[0009] Preferably, when the welding skin is 410 stainless steel, the composition of the flux core is calculated by mass fraction:
[0010] C: 0.50-0.90%; Si: 0.36-0.86%; Mn: 2.55-3.55%; Cr: 40.20-45.20%; Ni: 5.25-7.25%; Mo: 6.00-8.00%; Nb: 4.00-6.00%; Cu: 3.20-4.50%; the balance is Fe.
[0011] Preferably, when the weld skin is 430 stainless steel, the composition of the flux core is, by mass fraction, C: 0.50-0.90%, Si: 0.5-1.00%, Mn: 2.5-3.5%, Cr: 28.00-32.00%, Ni: 5.00-7.00%, Mo: 6.00-8.00%, Nb: 4.00-6.00%, Cu: 1.20-2.00%, and the balance is Fe.
[0012] Preferably, the filling rate of the flux core in the welding wire is 30-34wt.%.
[0013] Preferably, the diameter of the welding wire is 1.0-1.2 mm.
[0014] A method for preparing the above-mentioned metal flux-cored welding wire for laser cladding comprises the following steps:
[0015] Step 1, drying and mixing the weighed and mixed raw materials;
[0016] Step 2: placing the raw material in a stainless steel strip, wrapping the raw material with the stainless steel strip, and forming a welding wire of a size by drawing the stainless steel strip wrapped with the raw material several times.
[0017] Preferably, in step 1, the raw materials are heated by a vacuum heating furnace and mixed by a mixer.
[0018] Preferably, in step 2, the stainless steel strip is cleaned by alcohol removal before use.
[0019] Preferably, the metal flux-cored welding wire processes the surface of the hydraulic support of the coal mine by laser cladding to generate a cladding layer on the surface of the hydraulic support.
[0020] Preferably, the hardness of the cladding layer is HRC50, and the neutral salt spray corrosion resistance is greater than 1000 hours.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention discloses a metal flux-cored welding wire for laser cladding, which consists of flux powder and welding skin, wherein the flux powder is wrapped by the welding skin, and the flux powder consists of various metal components, so that the composition of the flux powder can be adjusted according to the requirements of the cladding layer. Aiming at the main failure factors in the service environment of hydraulic supports in coal mines: chloride ion corrosion and coal particle wear, a targeted cladding layer composition design is carried out. The present invention is designed with a high Cr content as the main content to resist chloride ion corrosion, and is designed to be strengthened by Mo and Nb combined solid solution, and resists the wear failure of coal particles by virtue of its multi-component composite strengthening effect. The flux powder formula, combined with 430 stainless steel strip or 410 stainless steel strip, innovatively adds Nb and Mo elements on the basis of traditional Cr and Ni element solid solution strengthening, so as to ensure the excellent corrosion resistance of the cladding layer while having a high hardness. Furthermore, the flux-cored welding wire of the present invention is specially designed for laser cladding. Compared with solid welding wire, the welding wire of the present invention uses metal powder as the main raw material of the powder. In the laser cladding manufacturing process, the melting efficiency of the wire can be significantly improved compared with solid welding wire. At the same time, because the core part of the welding wire is powdered, the powder is easy to melt when laser melting is used, and the formed molten pool has good fluidity. The microstructure and chemical composition of the cladding layer finally formed are uniform, and the grain size is smaller than the arc cladding layer. During the laser cladding process, the spraying is reduced, the smoke is less, the surface morphology of the weld is smooth, and the slag is less. The flux-cored welding wire proposed by the present invention is used for laser cladding to prepare corrosion-resistant and high-hardness laser cladding layers. The powder formula is easy to obtain, the wire production efficiency is high, the cost is low, and the application prospect is broad. The welding wire can also be used in traditional fusion welding methods such as TIG and MIG.
[0023] The present invention also discloses a method for preparing a metal flux-cored welding wire for laser cladding. The preparation method first wraps the raw material powder with a stainless steel strip, and then draws the stainless steel strip wrapped with the raw material powder into a welding wire that meets the size requirements through several drawing operations. The preparation method can prepare a welding wire with a diameter of The stainless steel wire material is used for laser cladding treatment of the surface of the hydraulic support cylinder. The invention optimizes the formula ratio so that the stainless steel wire material has excellent corrosion resistance and high hardness.
[0024] The present invention also discloses an application of a metal flux-cored welding wire for laser cladding. The present invention designs a reasonable cladding layer alloy system based on the material composition and organizational composition of the hydraulic support and the characteristics of the laser cladding process by deeply studying the service environment characteristics of the hydraulic support, thereby developing a welding material that meets the service requirements of the hydraulic support. The wire laser cladding layer prepared by the metal flux-cored welding wire provided by the present invention has high hardness and corrosion resistance. The coating hardness can reach about HRC50, and the neutral salt spray corrosion (NSS) resistance is more than 1000 hours, and no surface corrosion occurs. The H2S corrosion resistance of the laser cladding layer is qualified by the melt C method A result of GB / T 4157--2017 "Laboratory Test Method for Resistance of Metals to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment". The present invention uses wire in combination with a laser heat source to modify the surface of parts. The laser heat source has the advantages of high efficiency and concentrated heat source, so that the prepared cladding layer is dense, fine grains, and uniform organization. The wire has a simpler preparation process than powder, low cost, and high efficiency. Therefore, the surface cladding layer preparation using wire in combination with laser heat source has good performance, low cost and obvious market competitive advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The microstructure of the cladding layer of the flux-cored welding wire prepared in Example 2 of the present invention after laser cladding. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] One of the embodiments of the present invention discloses a metal flux-cored welding wire for laser cladding, which is mainly used for preparing a coating on the surface of a hydraulic support that is resistant to chloride ion corrosion and coal particle wear. The metal wire material for laser cladding of the present invention is a flux-cored welding wire, which belongs to the martensitic stainless steel type material. By adding alloy elements that improve strength and toughness, the material has good corrosion resistance while having high hardness and plastic toughness, so that it can be prepared into a metal wire material by drawing. The metal flux-cored welding wire has a diameter of Martensitic stainless steel laser cladding flux-cored welding wire.
[0028] The flux core is a powdered metal powder, and its specific composition can be adjusted according to demand. The weld skin is made of stainless steel, and can be a common stainless steel strip such as 410 stainless steel strip and 430 stainless steel strip. Based on the main technical concept of the present invention, technicians in this field only change the composition of the steel strip (for example, 430 stainless steel strip is replaced by 410 stainless steel strip, etc.) to cause the composition of the flux powder to change. However, when the chemical composition is the same after multi-layer cladding using the test method specified by the present invention, it still falls within the protection scope of the present invention.
[0029] Specifically, when 430 stainless steel strip is preferably used, the core is composed of the following raw material components by mass percentage:
[0030] C: 0.50-0.90%;
[0031] Si: 0.5-1.00%;
[0032] Mn: 2.5-3.5%;
[0033] Cr: 30.00-35.00%;
[0034] Ni: 5.00-7.00%;
[0035] Mo: 6.00-8.00%;
[0036] Nb: 4.00-6.00%;
[0037] Cu: 3.20-4.50%;
[0038] The balance is Fe.
[0039] The powder filling rate of the flux-cored welding wire is 30wt.%-34wt.%.
[0040] Specifically, when 410 stainless steel strip is preferably used, the core is composed of the following raw material components by mass percentage:
[0041] C: 0.50-0.90%;
[0042] Si: 0.36-0.86%;
[0043] Mn: 2.55-3.55%;
[0044] Cr: 40.20-45.20%;
[0045] Ni: 5.25-7.25%;
[0046] Mo: 6.00-8.00%;
[0047] Nb: 4.00-6.00%;
[0048] Cu: 3.20-4.50%;
[0049] The balance is Fe.
[0050] The powder filling rate of the flux-cored welding wire is 30wt.%-34wt.%.
[0051] Through the above-mentioned analysis of the stainless steel 410 steel strip and the stainless steel 430 steel strip and their corresponding flux core compositions, it can be seen that as the type of weld skin is adjusted, the composition of the metal flux core is also continuously adjusted, so that the composition requirements of the cladding layer can be finally met.
[0052] The composition of the metal cladding layer prepared by the above-mentioned metal cored welding wire is:
[0053] C: 0.17-0.26%
[0054] Si: 0.31-0.43%;
[0055] Mn: 0.95-1.21%;
[0056] Cr: 20.18-21.67%;
[0057] Ni: 1.53-2.08%;
[0058] Mo: 1.64-2.31%;
[0059] Nb: 1.03-1.68%;
[0060] Cu: 0.90-1.32%;
[0061] The present invention ensures the corrosion resistance of the material through the reasonable allocation of elements, and not only improves the hardness of the material, but also has good plasticity and toughness, which is convenient for drawing and preparing into wire. Compared with the existing martensitic stainless steel, the stainless steel component has excellent corrosion resistance and higher hardness, and ensures that the cladding layer does not crack. The specific functions of the main alloy elements in the metal wire material formula of the present invention are as follows:
[0062] Chromium (Cr): With the increase of chromium content in stainless steel, not only the corrosion resistance in oxidizing acid medium increases, but also plays an important role in improving the ability of stainless steel to resist local corrosion such as stress corrosion, pitting corrosion, crevice corrosion, etc. in chloride solution. In stainless steel with high chromium content, intermetallic compounds are easily formed in the steel under the influence of thermal stress, which not only reduces the plastic toughness and corrosion resistance, but also deteriorates the cold formability and weldability. Chromium forms carbides with carbon in stainless steel, which reduces the corrosion resistance of steel and causes intergranular corrosion. However, when the carbon content is constant, the intergranular corrosion sensitivity decreases with the increase of chromium content in steel. Chromium can significantly improve the high-temperature oxidation resistance, sulfidation resistance and high-temperature strength of stainless steel. Although the chloride ion corrosion resistance of the cladding layer is closely related to the content of Cr, when the Cr element is high, a large amount of ferrite structure will be present in the cladding layer, resulting in its hardness not being greatly improved. Therefore, the target structure of the cladding layer of the present invention is a martensitic stainless steel structure, and 28.00-32.00% of Cr elements are added to the powder with a 430 stainless steel strip and a filling rate of 30-34wt.%. 36.20-40.20% of Cr elements are added to the powder with a 410 stainless steel strip and a filling rate of 30-34wt.%.
[0063] Nickel (Ni): Nickel is an important alloying element in stainless steel after chromium. In order to resist corrosion in reducing acids and alkaline media, it is not enough for steel to contain only chromium. Nickel must be added to the steel. Nickel can promote the stability of the passivation film of stainless steel and improve the thermodynamic stability of stainless steel. Therefore, the coexistence of chromium and nickel in stainless steel can significantly enhance the stainless steel's rust resistance and corrosion resistance. Nickel is beneficial to the high-temperature oxidation resistance of stainless steel, but harmful to its high-temperature sulfidation resistance. Because nickel reacts with sulfur to easily form low-melting sulfides, and the formation of low-melting sulfides will significantly reduce the hot workability of steel. Nickel can significantly improve the plasticity and toughness of stainless steel, and can lower the brittle temperature of some stainless steels with brittle transition temperatures. Nickel can improve the cold formability and weldability of some stainless steels and reduce the cold work hardening tendency of austenitic stainless steels. Nickel can significantly reduce the sensitivity of some stainless steels to the precipitation of intermetallic compounds, thereby preventing and reducing their harmful effects. In the present invention, 5.00-7.00% of Ni element is added to the powder by using 430 stainless steel strip and 30-34wt.% filling rate. 1.26-2.76% of Ni element is added to the powder by using 410 stainless steel strip and 30-34wt.% filling rate.
[0064] Niobium (Nb): Niobium is a stabilizing element that strongly forms carbon and nitrogen compounds in stainless steel. It is mainly used to prevent the chromium in the steel from forming chromium carbides with carbon, which causes the chromium concentration to decrease, resulting in a decrease in corrosion resistance, especially intergranular corrosion. Titanium can also combine with sulfur in steel to form compounds to prevent pitting corrosion. In the present invention, 430 stainless steel strip or 410 stainless steel strip and a filling rate of 30-34wt.% are combined, and 4.00-6.00% of Nb elements are added to the powder.
[0065] Molybdenum (Mo): Molybdenum is also one of the important alloying elements in stainless steel. Studies have confirmed that in marine atmospheres, it is difficult to prevent stainless steel from rusting just by relying on chromium, and molybdenum must be added. However, the beneficial effect of molybdenum on the corrosion resistance of stainless steel is premised on the fact that the steel must contain sufficient chromium, and as the amount of chromium in the steel increases, the beneficial effect of molybdenum in the steel will also increase significantly. Molybdenum can significantly promote the enrichment of chromium in the passivation film, thereby enhancing the stability of the stainless steel passivation film, and significantly strengthening the corrosion resistance of chromium in the steel, thereby greatly improving the stainlessness and corrosion resistance of various types of stainless steel to various reducing acid media. As the amount of molybdenum increases, the corrosion rate of steel decreases and the corrosion resistance increases. Molybdenum in stainless steel can improve the repassivation ability of steel, and its ability to resist pitting and crevice corrosion is about three times that of chromium. In order to resist pitting and crevice corrosion, molybdenum is generally added to stainless steel. In the present invention, 430 stainless steel strip or 410 stainless steel strip and a filling rate of 30-34wt.% are combined, and 6.00-8.00% of Mo element is added to the medicine powder.
[0066] Copper (Cu): Copper can improve the stainlessness and corrosion resistance of stainless steel, especially in reducing media such as sulfuric acid. When copper and molybdenum are added to steel, the effect is better. Copper is dissolved in austenite, increasing the stability of supercooled austenite and shifting the C curve to the right. The effect on the cooling transformation of austenite is to increase the stability of supercooled austenite, reduce the initial temperature of martensite transformation, and finally refine the grain. Adding an appropriate amount of copper to stainless steel can improve the corrosion resistance of steel to Cl-. This is related to the fact that copper can promote the enrichment of chromium in the surface passivation film. Copper can significantly reduce the strength and cold work hardening tendency of stainless steel and improve the plasticity of steel. Copper is an important element that significantly improves the cold formability of various stainless steels. The dispersion and precipitation of copper-rich ε intermetallic compounds is the main means of strengthening copper-containing precipitation hardening stainless steel, and is also the reason why martensitic, ferritic and austenitic stainless steels obtain antibacterial properties. As the copper content in steel increases, the thermoplasticity of stainless steel decreases, thereby affecting the hot workability of steel. In the present invention, 430 stainless steel strip or 410 stainless steel strip and a filling rate of 30-34wt.% are combined, and 3.2-4.5% of Cu element is added to the medicine powder.
[0067] Carbon (C): Carbon is the most important alloying element in traditional martensitic stainless steel. The reasonable ratio of chromium and carbon in steel has resulted in three types of martensitic stainless steel: high, medium and low carbon. The role of carbon is to expand the austenite zone and improve the hardenability of steel. As the amount of carbon in the steel increases and the strength and hardness of martensitic stainless steel increase, the plasticity, toughness, corrosion resistance, cold formability and weldability of the steel decrease. Carbon can increase the strength of stainless steel, but significantly reduces the plasticity and toughness of steel. Carbon combines with chromium in steel to form chromium-rich carbides at the grain boundaries, causing chromium depletion and causing intergranular corrosion and decreased corrosion resistance. In the present invention, 430 stainless steel strip or 410 stainless steel strip and a filling rate of 30-34wt.% are combined, and 0.5-0.90% of C element is added to the powder.
[0068] Silicon (Si) and manganese (Mn): Si and Mn have a combined deoxidation effect, which can reduce the oxygen content in the cladding layer, prevent the generation of pores, and also improve the hardness of the cladding metal. However, Mn is an austenite-forming element, so its content should be controlled. A large amount of Si addition will deteriorate the plasticity and toughness of the cladding layer, which also needs to be controlled. In the present invention, 0.50-1.00% of Si element and 2.50-3.50% of Mn element are added to the powder in combination with 430 stainless steel strip and a filling rate of 30-35wt.%. In combination with 410 stainless steel strip and a filling rate of 30-32wt.%, 0.87-1.11% of Si element and 2.55-3.55% of Mn element are added to the powder.
[0069] One embodiment of the present invention discloses a method for preparing a metal cored welding wire for laser cladding, the preparation process comprising the following two steps:
[0070] Step 1, according to the material type of the weld skin and the component content of the target cladding layer, determine the composition of the metal core, weigh the corresponding metal powder, mix the weighed metal powder by a mixer or other mixing method, and then dry it in a vacuum heating furnace to remove moisture from the mixed metal powder;
[0071] Step 2: Place mixed metal powder in the corresponding stainless steel weld skin. The stainless steel weld skin wraps and fixes the mixed metal powder to form a strip. The strip is drawn to form a welding wire with composite size requirements. The drawing process makes the mixed metal powder in the stainless steel weld skin denser.
[0072] The invention discloses a use of a chloride ion resistant high hardness martensitic laser cladding flux-cored welding wire, wherein the laser cladding metal flux-cored welding wire is used to prepare a diameter The laser cladding wire is used for laser cladding treatment of the surface of the hydraulic support cylinder.
[0073] Further, according to the use of a high-hardness martensitic laser cladding flux-cored welding wire resistant to chloride ions described in the present invention, after the laser cladding wire is laser clad on the surface of the hydraulic support cylinder, the surface hardness can reach 50HRC, and the material has excellent resistance to chloride ion corrosion. Under the conditions of "GBT10125 Artificial Atmosphere Corrosion Test Salt Spray Test", when tested in a neutral salt spray corrosion test, the corrosion rating of the surface of the material after 1000 hours of corrosion can reach the highest level 9 or above according to "GBT6461 Rating of samples and test pieces of metals and other inorganic coverings on metal substrates after corrosion tests" .
[0074] The implementation effects of the present invention are described below in conjunction with specific embodiments.
[0075] Embodiment 1:
[0076] The composition formula of the powder shown in Example 1 is shown in Table 1:
[0077] Table 1. Example 1 powder ingredients formula
[0078] C Si Mn Cr Ni Mo Nb Cu Fe 0.5 1 2.5 30 5.0 6.0 6.0 3.2 Bal.
[0079] The powder formula of Example 1 was used, and 430 stainless steel strip was used for wrapping. The filling rate of the powder was controlled at 30wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the obtained cladding layer was shown in Table 2:
[0080] Table 2. Surface hardness of materials in Example 1
[0081]
[0082] Example 1 The wire is TIG welded with multiple layers (not less than 5 layers), and the rating results are shown in Table 3 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0083] Table 3. Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 1
[0084]
[0085] Case 1: The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 4:
[0086] Table 4. Cladding metal composition of Example 1
[0087] C Si Mn Cr Ni Mo Nb Cu Fe 0.18 0.42 0.97 20.18 1.55 1.64 1.65 0.9 Bal.
[0088] Embodiment 2:
[0089] The composition formula of the powder shown in Example 2 is shown in Table 5:
[0090] Table 5. Example 2 powder composition formula
[0091] C Si Mn Cr Ni Mo Nb Cu Fe 0.9 0.5 3.5 35.0 6.3 7.0 4.0 4.5 Bal.
[0092] The powder formula of Example 2 was used, and the powder was wrapped with 430 stainless steel strip. The filling rate of the powder was controlled at 34wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the cladding layer was shown in Table 6:
[0093] Table 6. Surface hardness of materials in Example 2
[0094]
[0095] Example 2 The wire is TIG welded with multiple layers (not less than 5 layers), and the rating results are shown in Table 7 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0096] Table 7. Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 2
[0097]
[0098] Case 2: The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 8:
[0099] Table 8. Cladding metal composition of Example 2
[0100] C Si Mn Cr Ni Mo Nb Cu Fe 0.26 0.32 1.21 21.59 1.78 1.93 1.07 1.31 Bal.
[0101] Embodiment 3:
[0102] The composition formula of the powder shown in Example 3 is shown in Table 9:
[0103] Table 9. Example 3 powder composition formula
[0104] C Si Mn Cr Ni Mo Nb Cu Fe 0.7 0.7 2.9 31.5 7 8 5.0 3.8 Bal.
[0105] The powder formula of Example 3 was used, and the powder was wrapped with 430 stainless steel strip. The filling rate of the powder was controlled at 32wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the cladding layer was shown in Table 10:
[0106] Table 10. Surface hardness of materials in Example 3
[0107]
[0108] Example 3 The wire is TIG welded with multiple layers (not less than 5 layers), and the rating results are shown in Table 11 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0109] Table 11. Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 3
[0110]
[0111] Case 3: The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 12:
[0112] Table 12. Cladding metal composition of Example 3
[0113] C Si Mn Cr Ni Mo Nb Cu Fe 0.21 0.37 1.12 20.89 2.04 2.31 1.42 1.20 Bal.
[0114] The laser cladding layer prepared in Example 3 has a structure as follows Figure 1 As shown: the cladding layer is mainly composed of cellular dendrites, the structure is martensite, and the structure is evenly distributed.
[0115] Example 4
[0116] The composition formula of the powder shown in Example 4 is shown in Table 13:
[0117] Table 13 Powder ingredients formula
[0118] C Si Mn Cr Ni Mo Nb Cu Fe 0.8 0.8 3.0 33 6.5 7.5 4.5 4 Bal.
[0119] The powder formula of Example 4 was used, and the powder was wrapped with 430 stainless steel strip. The filling rate of the powder was controlled at 32wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the cladding layer was shown in Table 14:
[0120] Table 14. Surface hardness of materials in Example 4
[0121]
[0122] Example 4 The wire is clad with multiple layers (not less than 5 layers) by TIG welding, and the rating results are shown in Table 11 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0123] Table 15. Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 4
[0124]
[0125] Example 4 The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 16:
[0126] Table 16. Cladding metal composition of Example 3
[0127] C Si Mn Cr Ni Mo Nb Cu Fe 0.24 0.33 1.15 20.5 1.8 1.8 1.2 1 Bal.
[0128] Embodiment 5:
[0129] The composition formula of the powder shown in Example 5 is shown in Table 17:
[0130] Table 17. Example 5 powder composition formula
[0131] C Si Mn Cr Ni Mo Nb Cu Fe 0.5 0.86 2.55 45.2 5.25 6.0 4.0 4.5 Bal.
[0132] The powder formula of Example 5 was used, and the powder was wrapped with 410 stainless steel strip. The filling rate of the powder was controlled at 30wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the cladding layer was shown in Table 18:
[0133] Table 18. Surface hardness of materials in Example 5
[0134]
[0135] Example 5 The wire is clad with multiple layers (not less than 5 layers) by TIG welding, and the rating results are shown in Table 19 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0136] Table 19 Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 5
[0137]
[0138] Example 5 The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 20:
[0139] Table 20. Cladding metal composition of Example 5
[0140] C Si Mn Cr Ni Mo Nb Cu Fe 0.17 0.43 0.95 21.67 1.53 1.64 1.03 1.32 Bal.
[0141] Embodiment 6:
[0142] The composition formula of the powder shown in Example 6 is shown in Table 21:
[0143] Table 21. Example 6 powder composition formula
[0144] C Si Mn Cr Ni Mo Nb Cu Fe 0.9 0.36 3.55 43.5 7.25 7.0 6.0 3.8 Bal.
[0145] The powder formula of Example 6 was used, and the powder was wrapped with 410 stainless steel strip. The filling rate of the powder was controlled at 34wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the obtained cladding layer was shown in Table 22:
[0146] Table 22. Surface hardness of Example 6 materials
[0147]
[0148] Example 6 The wire material is clad by TIG welding for multi-layer cladding (not less than 5 layers), and the rating results are shown in Table 23 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0149] Table 23. Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 6
[0150]
[0151] Example 6 The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 24:
[0152] Table 24. Cladding metal composition of Example 6
[0153] C Si Mn Cr Ni Mo Nb Cu Fe 0.26 0.31 1.18 20.89 2.08 1.98 1.68 1.17 Bal.
[0154] Embodiment 7:
[0155] The composition formula of the powder shown in Example 7 is shown in Table 25:
[0156] Table 25. Example 7 powder composition formula
[0157] C Si Mn Cr Ni Mo Nb Cu Fe 0.68 0.58 3.0 40.2 6.1 8 5.0 3.2 Bal.
[0158] The powder formula of Example 7 was used, and the powder was wrapped with 410 stainless steel strip. The filling rate of the powder was controlled at 32wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the cladding layer obtained was shown in Table 26:
[0159] Table 26. Surface hardness of Example 7 materials
[0160]
[0161] Example 7 The wire material is clad by TIG welding for multi-layer cladding (not less than 5 layers), and the rating results are shown in Table 27 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0162] Table 28. Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 7
[0163]
[0164] Example 7 The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 29:
[0165] Table 29. Cladding metal composition of Example 7
[0166] C Si Mn Cr Ni Mo Nb Cu Fe 0.19 0.36 1.13 20.2 1.78 2.28 1.43 0.93 Bal.
[0167] Embodiment 8:
[0168] The composition formula of the powder shown in Example 8 is shown in Table 29:
[0169] Table 29. Example 8 powder composition formula
[0170] C Si Mn Cr Ni Mo Nb Cu Fe 0.6 0.75 3.2 42 6.5 6.5 4.5 3.7 Bal.
[0171] The powder formula of Example 8 was used, and the powder was wrapped with 410 stainless steel strip. The filling rate of the powder was controlled at 32wt.%, and a flux-cored welding wire was prepared by drawing. The flux-cored welding wire was used for laser cladding, and the hardness of the cladding layer obtained was shown in Table 30:
[0172] Table 30. Surface hardness of materials in Example 8
[0173]
[0174] Example 8 The wire material is clad by TIG welding for multi-layer cladding (not less than 5 layers), and the rating results are shown in Table 31 using the "GB / T4157 Laboratory Test Method for Metal Resistance to Sulfide Stress Cracking and Stress Corrosion Cracking in Hydrogen Sulfide Environment" and the "GB / T10125 Artificial Atmosphere Corrosion Test Salt Spray Test":
[0175] Table 31. Neutral salt spray and H2S corrosion resistance test results of the cladding layer of the material in Example 8
[0176]
[0177] Example 8 The wire is clad by TIG welding for multiple layers (not less than 5 layers). The cladding metal composition is shown in Table 32:
[0178] Table 32. Cladding metal composition of Example 8
[0179] C Si Mn Cr Ni Mo Nb Cu Fe 0.22 0.35 1.01 20.5 1.65 1.75 1.35 1.25 Bal.
[0180] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal cored welding wire for laser cladding, characterized in that: It includes a flux core and a welding skin, wherein the flux core is wrapped by the welding skin; the flux core is in powder form, and the welding skin is made of stainless steel; The metal flux-cored welding wire is used to prepare a cladding layer by laser cladding; the composition of the cladding layer is, by mass fraction, C: 0.17-0.26%; Si: 0.31-0.43%; Mn: 0.95-1.21%; Cr: 20.18-21.67%; Ni: 1.53-2.08%; Mo: 1.64-2.31%; Nb: 1.03-1.68%; Cu: 0.90-1.32%, and the balance is iron; When the weld skin is 410 stainless steel, the composition of the flux core is calculated by mass fraction: C: 0.50-0.90%; Si: 0.36-0.86%; Mn: 2.55-3.55%; Cr: 40.20-45.20%; Ni: 5.25-7.25%; Mo: 6.00-8.00%; Nb: 4.00-6.00%; Cu: 3.20-4.50%; the balance is Fe; When the weld skin is 430 stainless steel, the composition of the flux core is, by mass fraction, C: 0.50-0.90%, Si: 0.5-1.00%, Mn: 2.5-3.5%, Cr: 28.00-32.00%, Ni: 5.00-7.00%, Mo: 6.00-8.00%, Nb: 4.00-6.00%, Cu: 1.20-2.00%, and the balance is Fe; The cladding layer is on the surface of the hydraulic support.
2. The metal cored welding wire for laser cladding according to claim 1, characterized in that: The filling rate of the flux core in the welding wire is 30-34wt.%.
3. The metal flux-cored welding wire for laser cladding according to claim 1, characterized in that: The diameter of the welding wire is 1.0-1.2 mm.
4. A method for preparing the metal cored welding wire for laser cladding according to claim 1, characterized in that: The following steps are involved: Step 1, drying and mixing the weighed and mixed raw materials; Step 2: placing the raw material in a stainless steel strip, wrapping the raw material with the stainless steel strip, and forming a welding wire of a size by drawing the stainless steel strip wrapped with the raw material several times.
5. The method for preparing a metal cored welding wire for laser cladding according to claim 4, characterized in that: In step 1, the raw materials are heated by a vacuum heating furnace and mixed by a mixer.
6. The method for preparing a metal cored welding wire for laser cladding according to claim 4, characterized in that: In step 2, the stainless steel strip is cleaned by alcohol removal before use.
7. An application of the metal flux-cored welding wire for laser cladding according to claim 1, characterized in that: The metal flux-cored welding wire processes the surface of the hydraulic support of a coal mine by laser cladding, and generates a cladding layer on the surface of the hydraulic support.
8. The use of the metal flux-cored welding wire for laser cladding according to claim 7, characterized in that: The hardness of the cladding layer is HRC50, and the neutral salt spray corrosion resistance is greater than 1000 hours.
Citation Information
Patent Citations
15-5PH martensite precipitation hardening stainless steel metal core welding wire
CN112496592A
Welding wire for alloy steel-stainless steel composite material transition layer and preparation method of welding wire
CN114346512A